The Impact of Artificial Intelligence Integration on Enhancing Lecturers' Pedagogical Competencie - Melda Rumia Rosmery Simorangkir; Evi Deliviana; Dameria Sinaga (Al-Qalam Institue, 2026)
Higher education faces challenges in adapting to technological advancements, particularly the integration of Artificial Intelligence (AI) in teaching. This study aims to examine the impact of AI utilization and its integration into the curriculum on lecturers' teaching skills. The research employed a quantitative approach using a structured questionnaire and analyzed data with multiple linear regression. The findings reveal that AI integration into the curriculum has a significantly stronger impact on enhancing lecturers' teaching skills compared to the mere frequency of AI usage. Specifically, the integration of AI into curriculum design and instruction leads to more personalized, adaptive, and effective teaching practices. The study provides empirical evidence of the importance of embedding AI in curricula to foster pedagogical innovation. The research contributes to the ongoing discourse on AI in education by highlighting the need for structured AI-based pedagogical frameworks. It also calls for further research to explore the long-term effects of AI integration in diverse educational settings and to address the ethical implications of AI in educationt.